Effect of Brix Concentration and pH of Molassses Media on Ethanol Yield in The Fermentation Process at PT. Indo Acidatama. Tbk - Hutapea, Henny Parida; Ahmadi, Panji (Universitas Pendidikan Mandalika, 2024)
PT. Indo Acidatama Tbk. is a company that produces ethanol. Ethanol is produced by fermentation using molasses derived from sugar processing waste. To get the optimal ethanol content, it can be determined from the yield produced, it is necessary to have effectiveness in the fermentation process. In this experiment, the fermentation process was carried out with variations in molasses concentration and pH. The aim was to determine the combination of brix concentration and molasses pH in producing the most effective ethanol yield. The concentration of molasses used was 16 obrix, 20 obrix and 24 obrix. While the pH used was 4, 5 and 6. In the determination of the ethanol content, the separation was carried out by a distillation process, then the distilled ethanol was tested using a spindle alcoholmeter and a chromatographic test was carried out using a Gas Chromatography type 6890N. After getting the ethanol content, the next step is to determine the yield by using the alcohol content calculation. The results of the chromatography test obtained samples of 24 obrix variations and pH 4, getting the highest concentration, which was 3.05%. From the calculation of alcohol content, the sample variation of 16 obrix and pH 5 got the highest yield value, with an average of 26.74. From the results of the Two-Way ANOVA calculation, it was found that obrix and pH had a significant effect on ethanol yield.